Alcohol management practices in community sporting clubs: Validation of an online self‐report tool. (7th June 2018) - McFadyen, Tameka; Tindall, Jennifer; Wiggers, John; Kingsland, Melanie; Sherker, Shauna; Gillham, Karen; Rowland, Bosco; Heaton, Rachael; Lecathelinais, Christophe; Wolfenden, Luke
Abstract: Introduction and Aims: Those involved in organised sport have a high risk of excessive alcohol consumption and alcohol‐related harm, the implementation of alcohol management practices have been proven to reduce these risks. Measuring alcohol management practice implementation by sporting clubs is impeded by a lack of valid tools. The aim of this study was to determine the validity of online self‐report of alcohol‐management practices by community football clubs via comparison with observational methods. Design and Methods: A cross‐sectional study was undertaken with a sample of community football clubs within Australia. The implementation of 12 alcohol management practices was collected via: (i) an online survey; and (ii) observational audit at a clubs home ground. The prevalence of implementation of alcohol management practices for both data collection methods was calculated as was percent agreement and Kappa/Prevalence Adjusted and Bias Adjusted Kappa (PABAK) statistics. Results: Data were collected from 58 football clubs. For both assessment methods, implementation prevalence was greater than 80% for 6 of the 12 alcohol management practices. A total of 75% ( n = 9) of practices had at least 70% agreement between the online and observation methods of assessment. Kappa/PABAK scores ranged from −0.08 (poor agreement) to 0.97 (almost perfect agreement). Discussion and Conclusion: The online survey provided valid measure of assessing some but not all alcohol management practices in community sporting clubs. The validity of the measure may be improved by enhancements to the manner in which the self‐report data are collected.